ABCC9 mutations identified in human dilated cardiomyopathy disrupt catalytic K(ATP) channel gating - Bienengraeber, Martin (2004)
Stress tolerance of the heart requires high-fidelity metabolic sensing by ATP-sensitive potassium (K(ATP)) channels that adjust membrane potential-dependent functions to match cellular energetic demand. Scanning of genomic DNA from individuals with heart failure and rhythm disturbances due to idiopathic dilated cardiomyopathy identified two mutations in ABCC9, which encodes the regulatory SUR2A subunit of the cardiac K(ATP) channel. These missense and frameshift mutations mapped to evolutionarily conserved domains adjacent to the catalytic ATPase pocket within SUR2A. Mutant SUR2A proteins showed aberrant redistribution of conformations in the intrinsic ATP hydrolytic cycle, translating into abnormal K(ATP) channel phenotypes with compromised metabolic signal decoding. Defective catalysis-mediated pore regulation is thus a mechanism for channel dysfunction and susceptibility to dilated cardiomyopathy.